(3GdhGaj HGdhajGJs - (3Ydj Hf YHO GdcGaj Hf Ydj Hf JeGe GdSHcj GdCfUGQj GdNRQLj, CHh GdMSf, Jbqj GdOjf,J (B756 (3g` s
(3ChdgG (B:s
(3CeG HYO MeOkG ddg GdPi JaQO HGdHbGA agPg ChQGb GdJbWJ ajgG hajGJ GdCYjGf ef GdUMGHI hGdNdaGA s
(3BNQgG (B:s
(3jfJgi CKfGA hajGJ SfI CQHY hYTQjf heGFJjf HJQLeI CHj YHjO GdbGSe Hf SdGe s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B302s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ , HgG NQe s
(3GdfSNI HgG CQVg s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs